A study on the EBA stress test results: Influence of bank, portfolio and country-level characteristics - Javier Hernández; Javier Población García; Nuria Suárez; Javier Tarancón (European Central Bank (ECB), 2022)
The purpose of this paper is to investigate the main drivers of the change in the credit risk provisions at a portfolio level for the banks that have been subject of the 2018 EBA stress tests. Therefore, we perform a holistic review of the drivers of the three-year projections of credit losses. First, we define a model containing all the macroeconomic variables considered by the EBA methodological approach. By adding a three-dimension set of explanatory variables, entity-, banking sector- and portfolio-level aspects, we verify whether the published results show some kind of relation with these explanatory variables. Our results show that, although EBA variables explain most part of credit risk provisions, we obtain evidence about the role played by bank-level variables, banking sector features in each country, and the specific characteristics of the portfolio in explaining part of the provisions. Moreover, the results also indicate the existence of complementary/substitution effects of both bank- and portfolio-level variables with the characteristics of the banking sector when explaining credit risk provisions.
Keywords: G20; G21; G28; 330; Stress tests; credit risk; EBA; bank characteristics